Pelatihan Desain Grafis Untuk Pengeditan Photo Product Pada Siswa APHP SMK Terangbangsa Sebagai Calon Pelaku Wirausaha Kota Semarang - Eko Nur Wahyudi; Yunus Anis; Herny Februariyanti; Zuly Budiarso (LPPM STIKOM Tunas Bangsa, 2022)
Terang Bangsa Vocational School students are young people as the next generation and human resources for national development. Therefore it is necessary to have efforts, programs and activities that continuously involve the participation of all parties, including families, educational institutions, youth organizations, the community and especially the younger generation themselves. In Indonesia itself, graphic design is in great demand. Current design technology really supports image processing and design, software that supports graphic design, this is very supportive in growing the creative industry in Indonesia. Responding that the creative industry opportunities in graphic design are very large, this is what encourages using graphic design to support a profession or job. Based on the findings of the problem, a solution is offered to provide graphic design training with Photoshop to produce photography of food products to Terang Bangsa Vocational High School students as potential entrepreneurs to support their product promotion with the aim of providing debriefing for APHP level XII students of Terang Bangsa Vocational High Schools. If they graduate and become entrepreneurs, they can have skills in making photos. products for promotional media. The achievement target to be achieved is that APHP students Terang Bangsa Vocational High Schools have the ability to make food photography products to create attractive promotional media. While the achievement indicators to be achieved are APHP students Terang Bangsa Vocational High Schools having knowledge and skills in arranging shooting objects, being able to use smartphones to produce attractive product photos. The output of PkM students of Agricultural Product Processing Agribusiness (APHP)Terang Bangsa Vocational High Schools are able to use product photos on promotional media to support promotion, while the output for D3 Informatics Management PkM team of Unisbank is article in devotional journals.